Environmental Sustainability under the Impact of the Current Crises - Mravcová, Anna (Studia Ecologiae et Bioethicae, 2024)
The state of the environment is getting worse worsening, despite the efforts of international community and individual states aimed at its improvement and achieving environmental sustainability. Moreover, the current crises – the COVID-19 pandemic and the armed conflict in Ukraine – have many negative effects on these efforts. The main aim of this paper is to analyse the most significant impacts of these crises on achieving environmental sustainability. We assume that they have strongly negatively affected the progress towards this goal, which we see as very dangerous given the urgency of the environmental crisis and the severity of its consequences. The paper is divided into three parts. In the first part, we outline the importance of environmental sustainability, focusing on the profiling of environmental pillar of sustainable development. The second part focuses on the analysis and mapping of the most significant environmental impacts of the COVID-19 crisis and the armed conflict in Ukraine on the very achievement of environmental sustainability. In this part, we demonstrate that both crises have strongly negatively influenced it and set the global community back in these efforts. In the third part, the findings as well as several possible future strategies are discussed.